Methods of saponin purification from Quillaja sp. for vaccine adjuvant production - Morais, Victor; Suarez, Norma; Silveira, Fernando (Frontiers in Natural Products, 2025)
Saponins are natural glycosides found in many plant species; they have a hydrophobic region, consisting of a steroid or triterpenoid skeleton called an aglycone, and a hydrophilic region, consisting of sugar chains attached to the aglycone through ether or ester linkages. This combination of polar and nonpolar elements endows saponins with soap-like behaviour in aqueous solutions. Owing to their structural characteristics, the amphiphilic nature of saponins is responsible for their foaming properties, as well as other biological functions, including their haemolytic activity. The adjuvant properties of saponins were known many years ago, but only in recent years have saponins been approved for human vaccine use in this manner. Saponins from Quillaja saponaria bark are the only source of approved preparations for human use, but a related species, Quillaja brasiliensis, also contains similar saponin compositions that can be obtained from leaves. In this work, we describe the different preparations of saponins used for adjuvants and the purification methods used to obtain each saponin.